The mentalist. The seventh and final season [videorecording (DVD)]. - Baker, Simon, 1969-; Tunney, Robin; Kang, Tim, 1973- (Warner Bros. Entertainment, 2015)
The FBI's masterfully manipulative criminal consultant Patrick Jane is back for the seventh and final season of the clever crime series. Now that Agent Teresa Lisbon and Jane have confessed their love for one another, they must find a way to be partners in both their professional and personal lives as they begin their new relationship.